The financial crisis and DSGE models. A critical evaluation - Stelmach, Jerzy (Kryzys finansowy a modele DSGE. Krytyczna ocena, 2011)
The global financial crisis has spurred a critical debate about the state of macroeconomics as a discipline and prompted new research questions. The one of the strongest line of critique is directed toward the Dynamic Stochastic General Equilibrium (DSGE) models. In such a context, the aim of this article is twofold. First, to point out in a non-technical manner the main deficiencies of the DSGE modelling approach; particularly, with respect to the inadequate treatment of financial markets. Second, to provide the overview of some recent developments in this area. The conclusion of this paper is that despite the substantial advances in the DSGE methodology, many important challenges remain unaddressed
Ekonomia = Economics, 2011, Nr 2 (14), s. 68-77
Keywords: DSGE models; macroeconomics; financial crisis